CURRICULUM ADAPTATION FOR STUDENTS WITH SPECIAL EDUCATIONAL NEEDS - Maria Ramos de Oliveira Vargas, Aline (Revista Gênero e Interdisciplinaridade, 2024)
This article addresses a topic that is relevant to the present day and of paramount importance for regular schools, which is curricular adaptation for students with special educational needs, discussing the importance of specific training for teachers in regular schools who receive inclusive education students. To guarantee quality education. Its objective is to discuss how to promote social inclusion and at the same time guarantee quality education and guarantee equity, since the audience for special education has been increasing in regular schools. Therefore, curricular adaptation, appropriate strategies and methodology are extremely necessary, but this specific audience needs a more in-depth look on the part of the teacher. In this sense, it is observed that there is a need for continued training of teachers to guarantee quality education to all students without distinction.